2016
DOI: 10.1016/j.brs.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults Improve on Everyday Tasks after Working Memory Training and Neurostimulation

Abstract: Background Aging is associated with decline in executive function (EF), upper-level cognitive abilities such as planning, problem solving, and working memory (WM). This decline is associated with age-related volume loss and reduced functional connectivity in the frontal lobes. Cognitive training interventions aim to counter these losses but often fail to elicit benefits beyond improvements on trained tasks. Recent interventions pairing WM training with transcranial direct current stimulation (tDCS) have improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(139 citation statements)
references
References 67 publications
(58 reference statements)
6
133
0
Order By: Relevance
“…In short, we previously found that only high WM capacity younger adults, or more educated older adults benefited from a single session of tDCS (Berryhill & Jones, 2012; Jones, Gozenman, & Berryhill, 2015; also see: Berryhill, et al, 2014; Hsu, Juan, & Tseng, 2016; Jones, Gozenman, et al, 2015; London & Slagter, 2015). Our data suggest active tDCS may enhance training-related benefits by prolonging improved performance, as our most robust effects were apparent after a month of no contact (Jones, Stephens, et al, 2015; Stephens & Berryhill, 2016). There is consistency across laboratories, protocols, and tasks that stands in marked contrast to the single session tDCS studies which is highly variable that we argue contributes to debates regarding the effectiveness of tDCS when applied to cognitive tasks (see meta-analyses: Horvath, Forte, & Carter, 2015a, 2015b; Jacobson, Koslowsky, & Lavidor, 2012; Mancuso, Ilieva, Hamilton, & Farah, 2016; but see: Antal, Keeser, Priori, Padberg, & Nitsche, 2015; Berryhill & Jones, 2012; Berryhill, et al, 2014; Brunye, et al, 2014; Price & Hamilton, 2015).…”
Section: Introductionmentioning
confidence: 60%
“…In short, we previously found that only high WM capacity younger adults, or more educated older adults benefited from a single session of tDCS (Berryhill & Jones, 2012; Jones, Gozenman, & Berryhill, 2015; also see: Berryhill, et al, 2014; Hsu, Juan, & Tseng, 2016; Jones, Gozenman, et al, 2015; London & Slagter, 2015). Our data suggest active tDCS may enhance training-related benefits by prolonging improved performance, as our most robust effects were apparent after a month of no contact (Jones, Stephens, et al, 2015; Stephens & Berryhill, 2016). There is consistency across laboratories, protocols, and tasks that stands in marked contrast to the single session tDCS studies which is highly variable that we argue contributes to debates regarding the effectiveness of tDCS when applied to cognitive tasks (see meta-analyses: Horvath, Forte, & Carter, 2015a, 2015b; Jacobson, Koslowsky, & Lavidor, 2012; Mancuso, Ilieva, Hamilton, & Farah, 2016; but see: Antal, Keeser, Priori, Padberg, & Nitsche, 2015; Berryhill & Jones, 2012; Berryhill, et al, 2014; Brunye, et al, 2014; Price & Hamilton, 2015).…”
Section: Introductionmentioning
confidence: 60%
“…For example, there have been rapid consolidation effects where group differences only begin to emerge in the minutes or hours after stimulation, or become stronger/more robust with time (e.g., Clark et al 2012;Ehsani et al 2016;Hoy et al 2014;Javadi and Cheng 2013;Penolazzi et al 2013;Reis et al 2015). Similarly, overnight consolidation has been enhanced when performance is measured the next day, despite a lack of group differences on day 1 (Koyama et al 2015;Martin et al 2014), and even cognitive training studies that failed to show immediate tDCS-related enhancements have still demonstrated greater tDCS-related retention a couple months later (Jones et al 2015;Martin et al 2013;Stephens and Berryhill 2016).…”
Section: Experimental Evidencementioning
confidence: 99%
“…Despite the evidence in support of short, within-day spacing intervals, a number of successful intervention studies have been carried out using a once-daily approach (e.g., Alonzo et al 2012;Au et al 2016;Reis et al 2015;Reis et al 2009;Stephens and Berryhill 2016). Moreover, our own work demonstrated with a WM intervention that participants showed the greatest improvement after a weekend break (Au et al 2016), suggesting in addition to the meta-plasticity protocols that longer spacing intervals of several days can actually be beneficial for consolidation as well.…”
Section: Spacing Of Stimulationmentioning
confidence: 99%
“…In this regard the influence of the COMT Val108/158Met polymorphism on changes in cognitive stability and flexibility after a tDCS-enhanced working memory training was recently investigated. However, no effects were found most likely due to a different study design targeting lasting transfer effects and/or a rather small sample size (Stephens and Berryhill, 2016). Another study related effects of tDCS over the right dlPFC on response inhibition to psychopathic traits like coldheartedness, since there is an association between psychopathic personality traits and impaired response inhibition.…”
Section: Tdcs and The Catechol-o-methyltransferase (Comt)mentioning
confidence: 99%